A two-step iterative algorithm for nding common xed point of Bregman quasi strict pseudo-contraction mappings with applications - Ekuma-Okereke*, E.; Okoro†, F.M.; Abhulimen†§, C.E. (International Journal of Mathematical Analysis and Modelling, 2023)
Motivated by some results of authors in this direction, our purpose in this paper is to construct a two-step iterative algorithm with inertial extrapolation term deﬁned with respect to Bregman distance function for approximating common ﬁxed points of a ﬁnite family of a closed Bregman quasi strictly pseudo-contraction mappings when the intersection of its set is assumed to be non empty. We prove a strong convergence theorem for it under ﬂexible and relaxed conditions in real reﬂexive Banach space. Our algorithm is applied in solving ﬁnite convex feasibility and equilibrium problems in reﬂexive Banach space. Furthermore, we demonstrate numerical examples to justify the eﬃciency and implementability of our algorithms in a ﬁnite dimensional real Banach space. Our results improves, generalizes and complements other previously and recently cited results of some authors in the literature of our procedure. It is intended that our procedure complement our motivated result cited in the literature.